Bio-Fenton and Bio-electro-Fenton as sustainable methods for degrading organic pollutants in wastewater. (January 2018) - Kahoush, May; Behary, Nemeshwaree; Cayla, Aurélie; Nierstrasz, Vincent
Highlights: Bio-Fenton and bio-electro-Fenton processes are used for sustainable wastewater treatment. Factors like pH, temperature and the concentration of substrate and biocatalyst have a big impact on their efficiency. Various organic pollutants from industrial sources, like dyes and pesticides can be treated. The main challenge is to improve stability and life time of these methods. Abstract: In this paper, an overview of the bio-Fenton and bio-electro-Fenton processes for sustainable wastewater treatment is provided. These two methods have been used in recent years to treat many kinds of persistent pollutants while maintaining the sustainability in materials and power consumption compared to conventional methods, through efficient eco-designed systems. The different kinds of electrodes used for the bio-electro-Fenton are reviewed, along with the influencing factors affecting the efficiency of these methods, and the different designs used to construct the reactors. Moreover, the various organic pollutants from industrial sources, like effluents from textile and pesticides facilities, treated using these processes are also reported. However, the main challenge facing these technologies is to improve their performance, stability and lifetime to achieve more sustainable and cost-effective wastewater treatment on pilot and large scales. Hence, future perspectives and trends are discussed to overcome the drawbacks of these methods.